Evaluation of the Correlation Between Strength and Special Training Indicators in Mixed Martial Arts - Andrii Chernozub; Oleh Olkhovyi; Alla Aloshyna; Andrii Savenko; Ivan Shtefiuk; Ivan Marionda; Tetiana Khoma; Victoriya Tulaydan (OVS LLC, 2023)
Study purpose. To study the peculiarities of correlation between the maximum strength development and quantity of kicks in MMA using load regimes of different intensity and energy supply. Materials and methods. 75 athletes aged 19±0.7 practicing MMA for 4±0.8 years were examined and divided into 3 groups. During 12 weeks, group 1 athletes used low-intensity (Rа=0.53) load regime, group 2 - medium-intensity (Rа=0.65) and group 3 - high-intensity (Ra=0.72). The control of attacking kicks (front kick, reverse side kick, roundhouse kick) quantity with maximum force until full muscle fatigue for 20 s allowed to check special training. The level of strength training was evaluated by estimating the maximum strength development (1 RM) indicators. Non-parametric methods of mathematical statistics were used for data processing. Results. The indicators of special training showed the greatest increase by an average of 13.2% in group 3 athletes during 12 weeks. In the other two groups, the dynamics of the controlled indicator was 3.2 times smaller for a similar period of time. The maximum muscle strength indicator increased by 41.9% in group 3 athletes compared to the initial data. These changes are on average 1.5 times higher than the results recorded in athletes of groups 1 and 2. Despite the revealed growth of strength and special training indicators in MMA athletes, there was no strong correlation between them in any research group. Conclusions. Using high-intensity load regime in conditions of anaerobic-alactate mode of energy supply allowed achieving the greatest results in strength and special training indicators. However, the study did not show correlation between the increase in maximum strength development and quantitative indicators of attacking kicks. Further research will be focused on searching for more informative markers for assessing the training of athletes in MMA and adaptation processes using biochemical control methods.